The prevalence of modifiable risk factors for atherosclerosis in patients with myocardial infarction - K. A. Kireev (Кубанский научный медицинский вестник, 2016)
We have conducted the questionnaire survey of 200 patients with the final diagnosis of acute myocardial infarction. The age of patients ranged from 32 to 65 years, the average age was 50.4±1,4 years old. All the respondents had been living in Chelyabinsk and nearby towns. They have answered some questions relating to the the risk of developing atherosclerosis. The records indicated a high prevalence of chronic stress (72%), hypertension (67.5%), overweight (55%), smoking (49%), high cholesterol (42,5%). Less frequently: physical inactivity (20,5%), hyperglycemia (18.5%), poor nutrition (16,5%). Only 26% of the respondents associated the development of the disease with unhealthy lifestyle. Able-bodied citizens don't have enough information about risk factors of developing atherosclerosis and other diseases of the circulatory system. This fact should be taken into account by health care system (it is necessary to develop the preventive measures).